FORMATION OF MODERN COMPETENCES OF PERSONNEL IN THE CONTEXT OF ACTIVATION OF DIGITAL MARKETING OF ENTERPRISES - TYUKHTENKO, NATALIYA; SYNIAKOVA, KATERYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to the study of modern staff competencies in the field of digital marketing. The essence of digital marketing is defined and its main tools are systematized, which allow to realize the main advantages: reaching a wide audience, the ability to measure the effectiveness of events, the ability to combine online and offline tools. Approaches to grouping and classification of digital skills and competencies are considered. Based on the study of European standards, the essence of digital competence, specific digital skills and professional digital skills is studied. It is determined that digital competence is not limited to the possession and use of purely technical knowledge, skills and abilities, but involves other aspects of adequate behavior of the individual in the digital environment. The structure of the digital literacy model, which consists of digital knowledge, digital skills and digital competencies, is studied. The combination of components of digital literacy provides access, understanding and evaluation by users of digital technologies and tools, the creation of digital content to achieve personal and professional goals. The main trends in the development of digital marketing are systematized, which serve as a basis for determining the most relevant competencies: availability of digital marketing tools, entering the online market of offline players, minimizing the participation of intermediaries, transition to situational marketing, creating "phygital" interactions with users. A set of competencies of the enterprise necessary for the implementation of modern trends in digital marketing, which are grouped into groups: operational, technical and formal skills and competencies; information and cognitive competencies; digital communication competencies; digital content creation competencies, strategic skills and competencies.